Brands and branding - Brown, Stephen , 1955 March 23- (London : Sage, 2016)
This book introduces readers to the key components of brands and helps them to begin to make sense of them - what they are, what they do, why and how - using plenty of examples and references drawn from a wide range brands
1. Introduction -- 2. Components -- 3. Commandments -- 4. Constraints -- 5. Conclusion
Includes bibliographical references (274-276) and index
Keywords: Brand name products; Branding (Marketing)